PENINGKATAN MINAT BELAJAR SISWA DENGAN MENGGUNAKAN PENDEKATAN GAMIFIKASI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Rezky Aquanur; Mufarizuddin; Yusnira; Syahrial; Muhammad Syahrul Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the planning, implementation, and improvement of students' learning interest through a gamification approach. The method used is classroom action research (CAR) which is carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 15 fourth-grade students of UPT SD Negeri 003 Muara Uwai in the odd semester of the 2025/2026 academic year. Data were collected through observation of teacher activities, observation of student activities and observation of student learning interest, then analyzed descriptively quantitatively and qualitatively. The results of the study showed a gradual increase in student learning interest. In the initial condition, the average student learning interest was only 33% with a poor category. After the Gamification Approach was implemented, the results of cycle I meeting I increased to 47% with a still poor category, and cycle I meeting II to 60% with a still poor category. In cycle II meeting I the average value reached 80% with a good category, while in cycle II meeting II it increased to 93% with a very good category. Thus, it can be concluded that implementing the Gamification Approach can significantly increase the learning interest of fourth grade students at UPT SD Negeri 003 Muara Uwai, from the poor category to very good.